Role of churches in the rehabilitation of orphans and vulnerable children: case study ZAOGA child evangelism ministry - Chitima, Brian (Midlands State University, 2017)
The purpose of this research was to identify the role been played by ZAOGA FIF CEM in the rehabilitation of orphans and vulnerable children through the provision of their needs, the protection of their rights as well as the promotion of OVC participation in entrepreneual activities. Socio-eco-political, psychological, environmental and physical vulnerabilities of children have led to their exploitation and infringement of children’s rights and have costed the nation by reversal of its efforts of development. Particular attention was focused on the OVC’s institutionalized at the FIF children’s homes in Mtoko and Mutare, as well as children who were under foster care. Semi structured interviews and questioners were used to collect information from the respondents and outstanding success stories from the church records were used in this research. The role of the church has not only benefitted the OVC’s in the country but also complimented the efforts of the governments in trying to ensure that every child has his/her rights promoted so as to eradicate and curtail the vulnerabilities directly and indirectly affecting children.